The influence of disability on absenteeism: an empirical analysis using Spanish data - Carlos Garcia-Serrano; Miguel A. Malo (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Using data from the European Community Household Panel for Spain covering the period 1995-2001, this paper investigates the influence of disability on absenteeism reported by workers. Results show that workers with disabilities are absent more days than workers without disabilities. This finding holds even when individuals selfreported health, visits to doctors and nights spent in hospitals are included in the estimations. The total effect of disability on absenteeism amounts to a marginal increase of 6-10 days per year. Implications for labour policy are discussed.
Keywords: 330